Efektivitas Terapi dan Kejadian Tidak Dikehendaki Penggunaan Regimen Pengobatan Jangka Pendek pada MultiDrug-Resistant Tuberculosis: a Scoping Review - Yunilistianingsih - Yunilistianingsih; Vitarani Dwi Ananda Ningrum (Fakultas Farmasi Universitas Setia Budi, 2023)
The increase in Multidrug-resistant Tuberculosis (MDR-TB) is a global problem that must be addressed immediately. Duration of treatment, adverse events (ADRs) and medical costs can affect adherence and treatment success. This literature review was conducted to review the effectiveness and ADRs of short-term regimens (STR) in MDR-TB patients. We used PubMed, ScienceDirect, and Google Scholar to retrieve the relevant original articles on MDR-TB treatment with STR in English-language, published from 2018 through 2022. The keywords used in the search for articles are